Evaluation of recent glacier recession in the Cordillera Blanca, Peru (AD 1962–1999): spatial distribution of mass loss and climatic forcing - Mark, Bryan G. (2005)
Original abstract: We use a combination of aerial photogrammetry, satellite imagery, andd ifferential GPS mapping to quantify the volume of ice lost between AD 1962 and 1999 from three glaciers on Nevado Queshque in the Cordillera Blanca, Peru´ ( 101S). The largest averagedsurface lowering (thinning) occurredin the southwest aspect (22 m) andthe least in the eastern aspect (5 m). A heuristic sensitivity analysis indicates that 9.3Wm 2 was requiredto melt the total observedice loss and this can be explainedby sensible heat transfer relatedto a temperature rise of 1 1C, combinedwith a latent heat decrease relatedto a 0.14 g kg 1 increase in specific humidity. A first-difference analysis of temperature records from 29 stations in the Cordillera Blanca shows an average rising trend of 0.26 1C per decade over the 37 year interval, more than adequate to supply the hypothesized sensible heat transfer. A simple transmittivity model within a digital elevation model indicates solar radiation related to altered cloudiness was not a predominant climatic forcing. The distribution of glacier area with altitude calculated with the digital terrain model explains the observed asymmetrical ice melt.